The Role of Creative Economy in Increasing the Interest of Hotel Guests Based on Local Wisdom - Peggy Ratna Marlianingrum; Umi Hamidah (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The creative economy is one sector that is expected to become a pillar of the Indonesian economy in the future. The purpose of this study is to ascertain how the creative economy influences hotel visitors' levels of interest. The research method used is quantitative, the study used a questionnaire distributed to hotel visitors with a total of 100 samples. According to the findings and debate, there is a considerable and positive relationship between the importance of the creative economy and visitors' interest. Hotel management must increase promotion with creative economic activities that are developed especially in the culinary field, increasing local wisdom culture (such as the lenggang none dance, Japit Betawi), creativity and interior design innovation that is Instagram able.